Web Applications with Javascript or Java : Volume 1: Constraint Validation, Enumerations, Special Datatypes - Wagner, Gerd; Diaconescu, Mircea (De Gruyter Textbook, 2017)
Today, web applications are the most important type of software applications. This textbook shows how to design and implement them, using a model-based engineering approach that covers general information management concepts and techniques and the two most relevant technology platforms: JavaScript and Java. The book provides an in-depth tutorial for theory-underpinned and example-based learning by doing it yourself, supported by quiz questions and practice projects. Volume 1 provides an introduction to web technologies and model-based web application engineering, discussing the information management concepts of constraint-based data validation, enumerations and special datatypes. Volume 2 discusses the advanced information management concepts of associations and inheritance in class hierarchies. Web apps are designed using UML class diagrams and implemented with two technologies: JavaScript for front-end (and distributed NodeJS) apps, and Java (with JPA and JSF) for back-end apps. The six example apps discussed in the book can be run, and their source code downloaded, from the book's website. Gerd Wagner is Professor of Internet Technology at Brandenburg University of Technology, Germany, and Adjunct Associate Professor at Old Dominion University, Norfolk, VA, USA. He works in the areas of web engineering and modeling and simulation. Mircea Diaconescu is a Software Architect and Technical Team Leader at Entri GmbH, Berlin. He enjoys to work with the newest web technologies and to build Web of Things projects. Java, JavaScript/NodeJS and C# are his favorite programming languages.